Topical Ophthalmic Formulation of Trichostatin A and SurR9-C84A for Quick Recovery Post-alkali Burn of Corneal Haze - Roy, Kislay; Neerati, Prasad; Cheung, Chun Hei Antonio; Kanwar, Rupinder K.; Sandhir, Rajat; Kanwar, Jagat R. (Frontiers in Pharmacology, 2017)
Alkali burn injury is a true ocular emergency of the conjunctiva and cornea that requires immediate precision. Lack of an immediate therapy can lead to a substantial damage in the ocular surface and anterior segment further causing visual impairment and disfigurement. We explored the regenerative capability of dominant negative survivin mutant (SurR9-C84A) and histone deacetylase (HDAC) inhibitor trichostatin-A (TSA) in vivo, in a rat alkali burn model. A topical insult in rat eyes with NaOH led to degradation of the conjunctival and corneal epithelium. The integrity of the conjunctival and corneal tissue was increased by TSA and SurR9-C84A due to improved clathrin and claudin expressions. Wound healing was initiated by an increase in TGF-beta-1 and, increased endogenous survivin inhibited apoptosis post TSA and SurR9-C84A treatments. Protein expressions of fibronectin and alpha-integrin 5 were found to increase promoting corneal integrity. The cytokine analysis confirmed increased expressions of IL-1beta, IL-6, IL-12, IL-13, IFN-gamma, TNF-alpha, GMCSF, Rantes, and MMP-2, which were found to be significantly downregulated by the combined treatment of SurR9-C84A and TSA. The ocular and systemic pharmacokinetic parameters were measured post topical ocular administration of TSA and SurR9-C84A. The SurR9-C84A and TSA sustained relatively longer in the cornea, conjunctiva, and aqueous humor than in the tear fluid and plasma. Our results confirmed that a combination of TSA with SurR9-C8A worked in synergy and showed a promising healing and anti-inflammatory effect in a very short time against alkali burn. Therefore, a combination of TSA and SurR9-C84A can fulfill the need for an immediate response to wound healing in alkali burnt cornea. We also synthesized ultra-small chitosan nanoparticles (USC-NPs) targeted with alpha-SMA antibodies that can be used for delivery of TSA and SurR9-C84A specifically to the ocular burn site.